INFLUENCE OF PERSONALITY AND COMPETENCE ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) WITH MODERATE WORK ENVIRONMENT : (STUDY ON PUBLIC HEALTH CENTER AT WINONG 1 AND II ) - Suprapti, Suprapti; Rizal, Alimuddin (IJOSMAS, 2022)
The purpose of this study is to analyze the influence of personality on Organizational Citizenship Behavior (OCB), analyze the influence of competence on Organizational Citizenship Behavior (OCB), analyze the influence of personality on Organizational Citizenship Behavior (OCB) and analyze the influence of competence on Organizational Citizenship Behavior (OCB) in health workers at the Puskesmas. Winong 1 and II are moderated by the work environment. This research method is a quantitative method. The type of data in this research is trimer data. Primary data is data obtained from the answers to questionnaires from each respondent. Data obtained from ordinal scale data from the recapitulation of the questionnaire onliner variables of personality, competence and work environment as well as OCB in Puskesmas Winong I and II in Pati Regency. The population in this research is 115 employees at Winong I and II Puskesmas, Pati Regency. data from the entire population of 115 employees. Based on the results of research and data analysis, it can be concluded that Personality has a positive influence on Organizational Citizenship Behavior (OCB), Competence has a positive influence on Organizational Itizenship Behavior (OCB), Work environment moderates the influence of personality on Organizational Citizenship Behavior (OCB), Work environment moderates the influence of competence on the Organizational Citizenship Behavior (OCB) of employees